Developing smart sustainable libraries in higher education: A preliminary study - Yunus, Norhazura; Ismail, Mohd Nasir (Journal of Islamic, Social, Economics and Development, 2025)
his preliminary study explores the development of smart sustainable libraries in Malaysian public universities, emphasizing the integration a smart and sustainable practices to enhance library services and support the United Nations' Sustainable Development Goals (UNSDGs). The research begins with a qualitative study involving interviews with expert librarians, which is then validated through secondary data gathered from literature reviews. This process identifies critical gaps in awareness, implementation, and the interrelationship of smart and sustainable elements within academic libraries. Ethical values, such as access to information, privacy, and transparency, are essential to smart sustainable libraries' development. The findings suggest that while Malaysian university libraries are familiar with smart and sustainable concepts, there is a need for clearer implementation strategies and a deeper understanding of the synergistic relationship between smart technologies and sustainable practices. This study contributes to the ongoing discourse on library innovation, providing insights into the challenges and opportunities for developing technologically advanced, environmentally conscious, and socially equitable libraries. The research underscores the importance of ethical considerations in ensuring the responsible use of technology and fostering user trust, ultimately promoting sustainable development in higher education.